6,282? Because 5x12x5= 300 -2
298x21 = 6,258 + 24
=6,282
So,
Let x represent Joe's weight and y represent Jeff's weight.
"Joe weighs 20 lbs. less than twice Jeff's weight."
x = 2y - 20
"If Jeff would gain 10 lbs., then together they would weigh 250 lbs."
(y + 10) + x = 250
We now have our two open sentences.
x = 2y - 20
(y + 10) + x = 250
Get rid of parentheses.
x = 2y - 20
x + y + 10 = 250
We will use Elimination by Substitution.
2y - 20 + y + 10 = 250
Collect Like Terms.
3y - 10 = 250
Add 10 to both sides.
3y = 260
Divide both sides by 3.
![Jeff's\ weight = 86 \frac{2}{3} \ lbs.](https://tex.z-dn.net/?f=Jeff%27s%5C%20weight%20%3D%2086%20%5Cfrac%7B2%7D%7B3%7D%20%5C%20lbs.)
Substitute again.
![x = 2(86 \frac{2}{3} )-20](https://tex.z-dn.net/?f=x%20%3D%202%2886%20%5Cfrac%7B2%7D%7B3%7D%20%29-20)
Multiply.
![x = 173 \frac{1}{3} -20](https://tex.z-dn.net/?f=x%20%3D%20173%20%5Cfrac%7B1%7D%7B3%7D%20-20)
Subtract.
![Joe's\ weight = 153 \frac{1}{3}\ lbs.](https://tex.z-dn.net/?f=Joe%27s%5C%20weight%20%3D%20153%20%5Cfrac%7B1%7D%7B3%7D%5C%20lbs.)
Check.
"Joe weighs 20 lbs. less than twice Jeff's weight."
Jeff's weight times two is 173 and one-third.
20 lbs. less than that is 153 and one-third lbs. Check.
"If Jeff would gain 10 lbs., then together they would weigh 250 lbs."
86 and two-thirds + 10 = 96 and two-thirds.
96 and two-thirds + 153 and one-third equals 250 lbs. Check.
![Joe's\ weight\ is\ 153 \frac{1}{3} \ lbs.](https://tex.z-dn.net/?f=Joe%27s%5C%20weight%5C%20is%5C%20153%20%5Cfrac%7B1%7D%7B3%7D%20%5C%20lbs.)
Answer:
MN=9.1 cm
LM= 9.9 cm
Step-by-step explanation:
Answer:
Step-by-step explanation:
log(2)+log(8)
=
2
1.20412≠2
False